Fixed Lingual Mandibular Growth Modificator: a new appliance for Class II correction - Osama Hasan Alali (Dental Press Editora, 2013)
INTRODUCTION: This article demonstrates the description and use of a new appliance for Class II correction. MATERIAL AND METHODS: A case report of a 10-year 5 month-old girl who presented with a skeletally-based Class II division 1 malocclusion (ANB = 6.5º) on a slightly low-angle pattern, with ML-NSL angle of 30º and ML-NL angle of 22.5º. Overjet was increased (7 mm) and associated with a deep bite. RESULTS: Overjet and overbite reduction was undertaken with the new appliance, Fixed Lingual Mandibular Growth Modificator (FLMGM). CONCLUSION: FLMGM may be effective in stimulating the growth of the mandible and correcting skeletal Class II malocclusions. Clinicians can benefit from the unique clinical advantages that FLMGM provides, such as easy handling and full integration with bracketed appliance at any phase.